Topography and Climate Influence on Radial Growth and Climate Sensitivity of Conifer Tree Species in Kananaskis, Alberta - Lira, Selina Akhter (Arts, 2020)
High elevation temperate forest at its upper limit are delimited by temperature. Climate warming would impose changes by altering growth conditions in these previously constrained environments. Growth response to climate will vary depending on topography and tree species. A dendroclimatological approach was employed to investigate spatial (tundra, treeline and forest along with north and south aspect) and temporal (1900-2017) variations in climate-growth sensitivity of four tree species: subalpine fir, subalpine larch, Engelmann spruce, and lodgepole pine in Kananaskis, Alberta. Correlation analyses showed similar climate-growth sensitivity for subalpine fir and Engelmann spruce at forest and treeline sites. Lodgepole pine only found on south-facing forest sites was not comparable with other species, but subalpine larch growth sensitivity was different from subalpine fir and Engelmann spruce. Treeline and tundra sites were only responsive to temperature; while precipitation was negatively significant at forest sites. Moving interval analysis revealed increased sensitivity to summer and winter temperatures in recent years, which is attributable to the climate change induced temperature increase in the study area. Tree growth was determined by calculating basal area increment for the studied tree species at all sites. Overall, south-facing sites had higher growth rates across elevations. Engelmann spruce had the highest growth rate at treeline and forest sites. Given projected climate change induced temperature and precipitation in the study area, the greatest growth increase will likely be at treeline, specifically for Engelmann spruce. Forest sites wouldn’t likely change as much as treeline sites as the precipitation increase that would offset temperature induced growth increases. To conclude, topography will continue to be the determinant of climate-growth response in future. The interaction between topography with regional climate parameters makes for complex patterns of vegetation response in this region.